2015
DOI: 10.1016/j.endm.2015.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Properly colored and rainbow copies of graphs with few cherries

Abstract: Let G be an n-vertex graph that contains linearly many cherries (i.e., paths on 3 vertices), and let c be a coloring of the edges of the complete graph Kn such that at each vertex every color appears only constantly many times. In 1979, Shearer conjectured that such a coloring c must contain a properly colored copy of G. We establish this conjecture in a strong form, showing that it holds even for graphs G with O(n 4/3 ) cherries and moreover this bound on the number of cherries is best possible up to a consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The existence of rainbow copies of H in k ‐bounded edge colorings of K n was studied in , provided that k = O ( n /Δ 2 ). In , it was observed that similar techniques allow to replace K n by a graph G with δfalse(Gfalse)()1cfalse/normalΔn, for a sufficiently small constant c > 0.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of rainbow copies of H in k ‐bounded edge colorings of K n was studied in , provided that k = O ( n /Δ 2 ). In , it was observed that similar techniques allow to replace K n by a graph G with δfalse(Gfalse)()1cfalse/normalΔn, for a sufficiently small constant c > 0.…”
Section: Applicationsmentioning
confidence: 99%
“…Sudakov and Volec showed that there exist a graph H with maximum degree at most Δ and a 3.9 n /Δ 2 ‐bounded edge coloring of K n which does not contain a rainbow copy of H . Therefore this theorem is also tight up to constant factors.…”
Section: Applicationsmentioning
confidence: 99%
“…A hypergraph generalisation of finding properly coloured Hamilton cycle in locally k‐bounded edge‐coloured complete graphs has also been studied by Dudek, Frieze and Ruciński as well as Dudek and Ferrara . Recently, Sudakov and Volec proved that every locally n(500r34)‐bounded edge‐coloured Kn contains all properly coloured graphs with at most r paths of length two. This proved a conjecture of Shearer as well as improves results of Alon, Jiang, Miller, Pritikin and Böttcher, Kohayakawa and Procacci .…”
Section: Introductionmentioning
confidence: 99%